Peace Education: Philosophical Analysis and Review of Nonviolent Character Education Practices - Gultom, Benediktus Hasiholan; Haq, Mochamad Ziaul (Hanifiya: Jurnal Studi Agama-Agama, 2024)
This paper examines education with a modern philosophical analysis approach. From a phenomenological point of view, philosophy firmly shows that philosophy does not solely start from metaphysical conceptions but also always starts from contextual ones, which originate from actual or true events. The method of this writing is phenomenological based on developing thoughts about educational philosophy. From this literature review, the conclusion emerges that to overcome conflict with a non-violent mentality, education is believed to help humans develop a new mentality and character that allows humans to adapt to their social environment. Thus, in order for humans to comprehend one another and cultivate peace, they must be receptive to all possibilities within the framework of hermeneutics, including the historical background, which serves as the foundation. This paper contributes to a mindset that prioritizes openness to new ideas, remaining flexible and easy to adapt, change, and investigate routes that are rebuilt over time in accordance with the basic philosophy of humans as existentialist creatures.